TUC Union Yes campaign, 1990 (London, 1990)
1990 1980-95 "TUC Union Yes campaign, 1990" [BW0154], 1990, Trades Union Congress In 1990, the TUC launched the Union Yes campaign to promote trade union organisation and recruitment in Greater Manchester and the London Docklands area. As part of the campaign a Women's Help Bus offered information and advice on equal pay and other issues important for women workers. The Congress badge for 1990 also carried the Union Yes logo.